1999
DOI: 10.1139/z99-003
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of antennal sensilla of the female sphinx moth, Manduca sexta (Lepidoptera: Sphingidae). II. Auriculate, coeloconic, and styliform complex sensilla

Abstract: The antennal flagellum of the female sphinx moth, Manduca sexta, bears eight types of sensilla: two trichoid, two basiconic, one auriculate, two coeloconic, and one styliform complex. We previously described the fine structure of the trichoid and basiconic sensilla (Shields and Hildebrand 1999). In this paper, we describe one type of auriculate, two types of coeloconic, and one type of styliform complex sensilla. The auriculate (ear- or spoon-shaped) sensillum is a small peg that averages 4 µm in length, is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…4). In Manduca, the male antenna is less sensitive than the female antenna to plant volatiles, including c3HA (Fraser et al, 2003), and has fewer ORCs that respond to plant volatiles (Shields and Hildebrand, 1999). Thus, the differences in the sensitivity threshold might be attributable to differences in the number, but not in the type, of ORCs converging on the glomerulus.…”
Section: Discussionmentioning
confidence: 99%
“…4). In Manduca, the male antenna is less sensitive than the female antenna to plant volatiles, including c3HA (Fraser et al, 2003), and has fewer ORCs that respond to plant volatiles (Shields and Hildebrand, 1999). Thus, the differences in the sensitivity threshold might be attributable to differences in the number, but not in the type, of ORCs converging on the glomerulus.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there are about 3.3 × 10 5 ORCs associated with about 10 5 sensilla in males (Keil, 1989;Lee and Strausfeld, 1990;Oland and Tolbert, 1989;Sanes and Hildebrand, 1976). In both sexes, each annulus bears approximately 2,100 -2,200 sensilla (Lee and Strausfeld, 1990;Shields and Hildebrand, 1999b) and several sensillum types are located…”
Section: Antennal Structurementioning
confidence: 99%
“…In other studies, Cuperus (1983) and Cuperus et al (1983) found no sexual dimorphism with respect to the types of antennal sensilla of some Yponomeuta species, but did find a marked difference in the distribution of various types of these sensilla . Shields and Hildebrand (1999b) found that six of the seven types of sensilla (styliform complex not included) are most abundant on the dorsal surface of the female flagellum of M. sexta, (type-A trichoid, type-B trichoid, type-A basiconic, type-B basiconic, type-A coeloconic, and type-B coeloconic; Table 2). Lee and Strausfeld (1990), in contrast, found equal numbers of sensilla in male M. sexta on the ventral and dorsal surfaces ( Table 2).…”
Section: Distribution Of Sensillamentioning
confidence: 99%
See 1 more Smart Citation
“…A transmission electron microscope study in the tobacco hornworm, Manduca sexta L. (Lepidoptera: Sphingidae), suggested that olfactory molecules entered through the grooves in sensilla coeloconica (Shields & Hildebrand 1999). These results are further substantiated as at least some sensilla coeloconica in female P. xylostella appear to be related to oviposition because more sensilla coeloconica were present in female antennae than in male antennae, and a previous study showed that their numbers were highly correlated with oviposition preference (yan et al 2014).…”
mentioning
confidence: 99%